Religion in the Development Debate Relevance and Rationale - Haar, Gerrie ter (Ghana bulletin of theology, 2008)
This article considers the reasons why it is important to consider the role of religion in development. It shows that religious perspectives on development differ from the secular views that tend to dominate the development industry, focussing very largely on economic growth. Key development institutions are only slowly beginning to address this issue.